Traumatic pulmonary pseudocyst: An underreported entity. Issue 2 (February 2017) - Phillips, B.; Shaw, J.; Turco, L.; McDonald, D.; Carey, J.; Balters, M.; Wagner, M.; Bertellotti, R.; Cornell, D.L.; Agrawal, D.K.; Asensio, J.A.
Abstract: Background: Traumatic pulmonary pseudocysts (TPP) are underreported cavitary lesions of the pulmonary parenchyma that can develop following blunt chest trauma. Although the occurrence of traumatic pulmonary pseudocyst is rare, this condition should be considered in the differential diagnosis of any cavitary lesion. Awareness of this injury and its clinical significance is important for successful management in order to avoid medical errors in the course of treatment. Methods: A literature search was conducted through Medline using the key phrases "traumatic pulmonary pseudocyst" and "traumatic pneumatocele." Relevant articles, especially those with focus on diagnosis and management of traumatic pneumatocele in adults, were selected. Due to the scarcity of literature and lack of Level I evidence on this subject, studies published in any year were considered. Results: A search of "traumatic pulmonary pseudocyst" and "traumatic pneumatocele" yielded 114 studies. Most of these were excluded based on inclusion and exclusion criteria. Thirty-five articles were reviewed. The majority of these were individual case studies; only eight articles were considered large case studies (greater than eight patients). Conclusion: Traumatic pulmonary pseudocysts are lesions that occur secondary to blunt chest trauma. Diagnosis is based on a history of trauma and appearance of a cystic lesion on CT. Accurate diagnosis of traumatic pulmonary pseudocyst is imperative to achieve successful outcomes. Failure to do so may lead to unnecessary procedures and complications.